PENGEMBANGAN MEDIA PEMBELAJARAN KEARSIPAN DIGITAL BERBASIS WEBSITE - Nada Nur Izzati; Roni Faslah; Darma Rika Swaramarinda (Cahaya Ilmu Bangsa Institute, 2025)
This research aims to: (1) develop a web-based archives learning media, (2) determine the feasibility of Arsip Teladan as a web-based archives learning media, (3) describe and explain the usefulness of the Arsip Teladan application for users, (4) as a guide for using the Arsip Teladan application. The type of research used is research and development (RnD) using the ADDIE development method (Analysis, Design, Development, Implementation, Evaluation). This research only reached the development stage by testing the feasibility of Arsip Teladan as a archives learning media validated by media experts and material experts. Data collection techniques were carried out by means of observation and questionnaires. Data analysis was carried out with qualitative and quantitative analysis. Based on the research that has been done, the researcher gets the following results: (1) Arsip Teladan as a website-based archives learning media has been developed with the address https://s.id/ArsipTeladan, (2) based on the results of expert validation, it is known that Arsip Teladan is suitable for use with the results of the average score of media expert validation 97% with the category “Very Feasible” and the average score of material experts 97,1% with the category “Very Feasible” as learning media.